2008
DOI: 10.1007/s11596-008-0307-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of berberine on expression of hepatocyte nuclear factor-4α in rats with fructose-induced insulin resistance

Abstract: The effects of berberine on the expression of hepatocyte nuclear factor-4alpha (HNF-4alpha) in liver of rats with fructose-induced insulin resistance and the molecular mechanism of berberine preventing insulin resistance were investigated. The experimental animals were divided into two groups of 16 animals each. The control group received a control routine diet containing 60% carbohydrate, and the study group a high-fructose diet containing 60% fructose as the sole source of carbohydrate. At the end of 6 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Our finding in this study revealed that FDW consumption, in a month, induced insulin resistance index (IRI), hyperinsulinemia a serum proinflammatory cytokines values such as IL6 and TNF in male rats. These results were confirmed by previous studies indicating that fructose-fed and FDW cause central obesity, insulin resistance, and hyperinsulinemia to increase in rats [ 4 ]. Previous studies indicated that TNF serum concentration elevated and altered insulin signaling in skeletal muscles cell membranes in insulin resistance disorders (type II diabetes and MS), but Artemisia dracunculus L. extract improved insulin action by increasing insulin signaling in skeletal muscle [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our finding in this study revealed that FDW consumption, in a month, induced insulin resistance index (IRI), hyperinsulinemia a serum proinflammatory cytokines values such as IL6 and TNF in male rats. These results were confirmed by previous studies indicating that fructose-fed and FDW cause central obesity, insulin resistance, and hyperinsulinemia to increase in rats [ 4 ]. Previous studies indicated that TNF serum concentration elevated and altered insulin signaling in skeletal muscles cell membranes in insulin resistance disorders (type II diabetes and MS), but Artemisia dracunculus L. extract improved insulin action by increasing insulin signaling in skeletal muscle [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, there are associations among insulin resistance, abdominal obesity, and serum immune markers such as IL6 and TNF α [ 3 ]. Moreover, metabolic syndrome related to insulin resistance (IR) is a state in that insulin is higher than normal concentration and it plays an important role in the pathophysiology of most common human diseases such as type 2 diabetes mellitus, hypertension, and coronary heart disease [ 4 ]. A mixture of several botanical medicines is used to treat diabetes mellitus and insulin resistance accompanied by hypertension in fructose-fed rats (FFR) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that inhibiting phosphorylation of IKK β might be a cofactor of berberine in achieving its anti-inflammation and insulin-resistance-improving effects [22]. The latest study also proved that berberine could inhibit fructose-induced insulin resistance in rats possibly by increasing the expression HNF-4 α in liver [23]. HNF-4 α is a positive regulator of PEPCK so an increase of HNF-4 α would result in increased gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, berberine up-regulated multidrug-resistance transporter expression (Lin et al, 1999), and the induction of P-glycoprotein is partially regulated by PXR (Harmsen et al, 2010). Berberine also prevented fructose-induced insulin resistance in rat islet cells by promoting the expression of HNF4α (Gao et al, 2008). However, information about effects of berberine on these nuclear receptors as well as whether drug processing genes are altered after in vivo exposure is limited.…”
Section: Introductionmentioning
confidence: 99%